2016
DOI: 10.1158/0008-5472.can-15-1862
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting Hypoxia-Induced Bicarbonate Transport Acidifies Tumor Cells and Suppresses Tumor Growth

Abstract: Tumor hypoxia is associated clinically with therapeutic resistance and poor patient outcomes. One feature of tumor hypoxia is activated expression of carbonic anhydrase IX (CA9), a regulator of pH and tumor growth. In this study, we investigated the hypothesis that impeding the reuptake of bicarbonate produced extracellularly by CA9 could exacerbate the intracellular acidity produced by hypoxic conditions, perhaps compromising cell growth and viability as a result. In 8 of 10 cancer cell lines, we found that h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 46 publications
6
72
3
Order By: Relevance
“…In some hypoxic cancer cells CA9/12 produced extracellular HCO 3 − is retrieved to buffer cytosolic pH (19, 55) (Fig. 9A).…”
Section: Resultsmentioning
confidence: 99%
“…In some hypoxic cancer cells CA9/12 produced extracellular HCO 3 − is retrieved to buffer cytosolic pH (19, 55) (Fig. 9A).…”
Section: Resultsmentioning
confidence: 99%
“…A recent report demonstrated that genetic targeting of sodium bicarbonate transporters with siRNA could decrease the growth of U87 GBM cells in vitro and in vivo (51). These data suggest that it will be important to consider the entire carbonic anhydrase-bicarbonate transporter system and its effects on TMZ treatment in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally reported that HIF-1α is constitutively expressed in many solid tumors2526. HIF-1 regulate hundreds of downstream genes, most of which are closely related to tumor growth, metastasis, and invasion27, as well as chemoresistance and radioresistance28.…”
Section: Discussionmentioning
confidence: 99%